A review of entrepreneurship education research: Exploring the contribution of the Education + Training special issues. Issue 3 (6th March 2018) - Henry, Colette; Lewis, Kate
Abstract : Purpose: The purpose of this paper is to review recent published research on entrepreneurship education (EE) specifically within the special issue collections of the journal Education +Training, and to assess the overall contribution to the field. The research questions focus on: What topics are explored by these SI papers? What trends can be observed in relation to country context and methodological approach? How is EE defined in these papers, and how do the papers contribute to the wider entrepreneurship research agenda? Design/methodology/approach: The paper uses an adapted version of the systematic literature review approach, focusing on the discrete special issues on entrepreneurship/enterprise education published in the journal Education + Training since 2010. A comprehensive reading guide was used to review the papers, with completed data compiled into a single excel spreadsheet to facilitate analysis. A total of 66 papers were reviewed. Findings: A considerable range of themes, geographical contexts and methodological approaches were used in the papers reviewed. A mix of qualitative and quantitative approaches were also found. The papers were characterised by a strong international and applied dimension, with the core collective contribution of the SI papers laying in their direct relevance to practice. Research limitations/implications: The paper is limited by its deliberate focus on a discrete set of special issue papers; however, the total of 66 papers included in the review is noteworthy. Practical implications: The paper demonstrates the considerable learning that can be garnered from the Education + Training special issue collection for EE practitioners. Originality/value: To the authors' knowledge, this is the first time this discrete collection of special issue papers has been reviewed.